2022
DOI: 10.1021/acs.organomet.2c00366
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Straightening Polymerization of Olefins to Form Polar Functionalized Semicrystalline Polyethylene

Abstract: We report the design and synthesis of an α-diimine Pd II catalyst that copolymerizes functionalized and long chain αolefins to produce semicrystalline polyethylene materials. Through a chain-straightening polymerization mechanism, the catalyst afforded high-melting point polymers with T m values of up to 120 °C. The chain-straightening polymerization operates with high [ω,1]-insertion selectivity at high alkene concentrations and with varying α-olefin chain lengths, including propylene. The Pd catalyst can cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…[ 1‐3 ] To this end, tremendous efforts have been devoted to designing novel ligands containing multiple sterically bulky substituents, as these bulky substituents have been found to facilitate the suppression of chain transfer. [ 4‐26 ] In the case of imine‐based late‐transition‐metal catalysts, the evolution of o ‐aryl substituents has endowed this type of catalysts with the capability to produce high molecular weight and even UHMWPE (ultra‐high molecular weight polyethylene) (Chart 1). Taking salicylaldimine Ni(II) system as an example, replacing the o ‐aryl ‐iso propyl moieties in the nickel complex with bulkier o ‐aryl‐dibenzhydryl or o ‐aryl‐dibenzosuberyl substituents provides gradually improved molecular weights of the resulting polyethylenes (Scheme 1).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 1‐3 ] To this end, tremendous efforts have been devoted to designing novel ligands containing multiple sterically bulky substituents, as these bulky substituents have been found to facilitate the suppression of chain transfer. [ 4‐26 ] In the case of imine‐based late‐transition‐metal catalysts, the evolution of o ‐aryl substituents has endowed this type of catalysts with the capability to produce high molecular weight and even UHMWPE (ultra‐high molecular weight polyethylene) (Chart 1). Taking salicylaldimine Ni(II) system as an example, replacing the o ‐aryl ‐iso propyl moieties in the nickel complex with bulkier o ‐aryl‐dibenzhydryl or o ‐aryl‐dibenzosuberyl substituents provides gradually improved molecular weights of the resulting polyethylenes (Scheme 1).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Our preliminary results suggested that the catalyst’s structural symmetry might also play a crucial role in tuning the polyethylene branching density, which is the first reported case to our knowledge. This is different from the previously reported cases in which the control of polyethylene branching density was accomplished by ligand electron or steric modulation or other weak neighbor-group interactions. For example, we have integrated the bulky ortho N -aryl substituents (naphthyl and benzothienyl groups) into the axial positions of the α-diimine Pd­(II) complexes, which could effectively suppress chain walking during the polymerization process, to obtain high-molecular-weight semi-crystalline polyethylene ( T m up to 123 °C) . Moreover, Liu and Harth et al recently reported that the m -xylyl substituents in the α-diimine Pd­(II) complex could also yield low-branched semi-crystalline polyethylene with high molecular weight ( T m up to 112 °C) .…”
Section: Resultsmentioning
confidence: 77%
“…51 Recently, Gao and Coates reported symmetrical α-diimine Ni(II) and Pd(II) catalysts with a DBB "sandwich" structure (Scheme 1, VII). 52,53 The Ni(II) catalyst generated unexpected moderately branched polyethylenes due to the noncovalent π-interactions between the Ni(II) center and the phenyl substituent on 8-p-tolylnaphthylimine moieties, 52 while the Pd(II) catalyst could copolymerize long chain α-olefins with functionalized long chain α-olefins to form functionalized semicrystalline polyethylenes through chain-straightening selectivity. 53 Bis(arylimino)acenaphthene (BIAN) pro-ligands with a planar acenaphthyl backbone have been widely employed to synthesize various α-diimine Ni(II) and Pd(II) catalysts.…”
Section: Introductionmentioning
confidence: 99%